THE EFFECT OF ADDITION 5% PROPOLIS NANOPARTICLES IN EPOXY RESIN AND BIOCERAMIC SEALERS ON THE GROWTH OF ENTEROCOCCUS FAECALIS ATCC 29212 AND THE DENTINAL TUBULAR PENETRATION: IN VITRO - WAHYUNI, NELMI; YANTI, NEVI; ABIDIN, TRIMURNI; PRASETIA, WIDI; SURYANTO, DWI (International Journal of Applied Pharmaceutics, 2023)
Objective: The goal of endodontic treatment is to eliminate bacteria and their products from the root canal. Bacteria are the main etiological factors of pulpal and periapical diseases. Chemomechanical preparation and administration of root canal medicaments cannot completely eliminate bacteria in the root canal system, especially Enterococcus faecalis, which have high resistancy, therefore, an ideal obturation material is required. Adequate root canal filling quality affects the success of endodontic treatment. The aim of this study was to observe the effect of addition 5% propolis nanoparticles to the commercial epoxy resin and the bioceramic sealer on the growth of E. faecalis ATCC 29212 and the dentinal tubular penetration. Methods: Thirty-five tooth samples were randomly divided into 5 groups. Root canal preparation was carried out with the same working length of 14 mm by cutting the tooth at the Cementoenamel Junction (CEJ); sample was inoculated with E. faecalis ATCC 29212 for 48 h. Obturation used four types of sealer, Group I (epoxy resin with 5% propolis nanoparticles), Group II (bioceramic with 5% propolis nanoparticles), Group III (bioceramic) and Group IV (epoxy resin). Data were analyzed using the Kruskal wallis test with a significant level of p<0.05. Results: In the bacterial growth test, there was a significant difference in the number of bacterial colonies between the epoxy resin groups with 5% propolis nanoparticles, bioceramic with 5% of propolis nanoparticles, bioceramic and epoxy resin (p = 0.000<0.05). In the dentinal tubular penetration there was a significant difference between epoxy resin with 5% of propolis nanoparticles, bioceramic sealer with 5% propolis nanoparticles, bioceramic, and epoxy resin (p = 0.001<0.05). Conclusion: The addition of 5% propolis nanoparticles to commercial bioceramic and epoxy resin sealers can eliminate E. faecalis bacteria in the root canals and increase dentinal tubular penetration. Bioceramic sealer has a higher antibacterial effect and dentinal tubular penetration compared to epoxy resin.